KONSEP SERTA IMPLEMENTASI MERDEKA BELAJAR PADA EVALUASI PELAJARAN PENDIDIKAN AGAMA ISLAM - Endang Retnowati; Risnawati Risnawati; Miftahir Rirqa; Nur Azizah (LPPM STAI Ihyaul Ulum Gresik, 2025)
This paper plans to decide the impact of the idea of merdeka belajar and its suggestions in the assessment of Islamic Strict Training Learning. This paper utilizes a subjective methodology and writing concentrate on strategies. In light of the consequences of the conversation, assessment comprises of estimation and evaluation. With regards to learning, assessment has a vital and key position, since it is remembered for the learning steps. The point is to decide the adequacy and proficiency of the learning framework. The degree remembers assessment for learning programs, growing experiences, and learning results. By and large, the assessment standards comprise of progression, exhaustive, fair, goal, agreeable, and commonsense. In particular, the standards comprise of lucidness, rationality, teaching method, and responsibility. In light of the writing audit that has been done, the strategy of the Service of Training and Culture, Nadiem Makarim, is known as the